2016
DOI: 10.1186/s12711-016-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing new candidate genes for reproductive traits in pigs: combining Bayesian GWAS and functional pathways

Abstract: BackgroundReproductive traits such as number of stillborn piglets (SB) and number of teats (NT) have been evaluated in many genome-wide association studies (GWAS). Most of these GWAS were performed under the assumption that these traits were normally distributed. However, both SB and NT are discrete (e.g. count) variables. Therefore, it is necessary to test for better fit of other appropriate statistical models based on discrete distributions. In addition, although many GWAS have been performed, the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 78 publications
(93 reference statements)
4
46
0
Order By: Relevance
“…The concept that additional mammary glands arise from somite division in the developing embryo is supported by the effects of the VRTN gene that were observed on vertebra number and teat count [6, 12, 16, 17, 23] and of the NR6A1 gene on SSC1 [6]. However, since genetic variation within NR6A1 is only observed in crosses between Asian and European breeds, we were not able to evaluate this result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept that additional mammary glands arise from somite division in the developing embryo is supported by the effects of the VRTN gene that were observed on vertebra number and teat count [6, 12, 16, 17, 23] and of the NR6A1 gene on SSC1 [6]. However, since genetic variation within NR6A1 is only observed in crosses between Asian and European breeds, we were not able to evaluate this result.…”
Section: Discussionmentioning
confidence: 99%
“…Putative causative genetic variations for vertebra number in the NR6A1 gene [14] on SSC1 and the VRTN gene [15] on SSC7 have been associated with variation in teat number in Meishan × occidental cross populations [6, 12]. VRTN has also been associated with teat number in commercial swine populations [13, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…In humans, it was shown that mutations in RIPPLY2 are associated with segment defects of the vertebrae [41]. In pigs, Verardo et al [42] reported that SYNDIG1L was associated with number of teats while Duijvesteijn et al [43] showed that number of teats and number of vertebras were controlled by several pleiotropic coding genes. These findings suggest that SYNDIG1L may have a role in the development of vertebrae in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Another GWAS, using 32,911 SNPs on 1550 Large White pigs, reported 21 QTL with additive effects on chromosomes 6, 7 and 12, one QTL with a dominant effect on chromosome 4, and identified VRTN as the most promising candidate gene for teat number [3]. A third GWAS using 41,647 SNPs on 1657 Large White pigs found 65 significant SNPs on chromosomes 1, 2, 7, 8, 12 and 14, including SNPs in the region 102.9 between 105.2 Mb on chromosome 7 [4]. A fourth GWAS using 39,778 SNPs identified the VRTN gene with pleiotropic and desirable effects on thoracic vertebral number, teat number and carcass (body) length across four pig populations, and showed that, of all SNPs on chromosome 7, a SNP within the VRTN gene had the most significant effect on teat number in Duroc pigs [5].…”
Section: Introductionmentioning
confidence: 99%
“…A GWAS using the porcine 60 K SNP chip on a F2 population from a cross between Landrace and Korean pigs identified highly significant SNPs on chromosome 7 that were more than 40 Mb away from the VRTN gene [6], and in another GWAS using 36,588 SNPs and 1024 Duroc pigs, the most significant SNPs on chromosome 7 were found 2 to 3 Mb downstream of the VRTN region [7]. However, other than for the VRTN region, there is little consensus among the GWAS results on genomic regions that affect teat number [24, 6, 7]. Therefore, additional studies are needed to identify the genetic factors that affect swine teat number.…”
Section: Introductionmentioning
confidence: 99%